Comprehensive analysis of stability and strength of thin-walled reinforced concrete elements based on energy approaches - Myroshnichenko, Ivan (Academic journal Industrial Machine Building Civil Engineering, 2025)
This work develops and substantiates a comprehensive engineering method for the analysis of thin-walled reinforced concrete beams with a cross-sectional width of b = 40 mm, which unifies the verification of the stability of the plane form of bending and the evaluation of torsional deformability. The relevance of the research is driven by the need to refine the limit states for elements with a depth-to-width ratio of h/b ≈ 5.5, where classical methods fail to fully account for the interaction between flexural and torsional stiffness in the cracked stage. The methodological basis of the study is the energy invariance hypothesis, allowing the replacement of a real cracked reinforced concrete element with an equivalent elastic model accumulating similar potential strain energy. The paper combines a modified Prandtl-Vlasov algorithm for determining the critical buckling moment with an analytical model of torsional compliance accounting for discrete crack distribution. A key feature of the methodology is the detailed consideration of the dowel action of the longitudinal reinforcement, treated as a beam on an elastic foundation, which provides resistance to the mutual shear displacement of crack faces and significantly influences the effective torsional stiffness, GJeff. A comparative analysis established that increasing the width to 40 mm leads to an almost twofold increase in the out-of-plane moment of inertia, Iy, and the critical moment, Mcr. It is proven that such a change in geometry shifts the structural behavior from the risk zone of sudden (brittle) buckling, characteristic of narrower beams, to the zone of plastic failure along the normal section, where the stability safety factor exceeds unity. Furthermore, adjusted values of the reduction factor, kred, are proposed, accounting for the decreased sensitivity of the wider cross-section to initial geometric imperfections and concrete creep deformations